Spatial Confinement of Optical Phonons in ZnO Nanowalls and Nanorods - M. Arora; R.P. Pant (Журнал нано- та електронної фізики)
FT Raman spectrum of ZnO nanowalls and nanorods showed optical phonon and multiphonon peaks of E2 (high) and E2 (low), E1 (TO and LO) and A1 (TO and LO), 2E2, [E2 + A1(LO)], [E1 (LO) + A1(TO)] and [E1(TO) + A(LO)] modes at (108.9 and 434.46 cm-1), (415.24 and 583.32), (383.49 and 574.84), 215.43, 676.24, 956.02 and 998.98 cm-1 respectively. In nanowalls, the appearance of B2 Raman inactive mode at 276.46 cm-1 is attributed to the existence of built in electric field in the crystallites of ZnO. The weak bands at 516.78 and 467.56 cm –1 confirmed the presence of highly localized modes near the grain boundaries having electric field within the grains close to grain boundary The broadening and asymmetry of the first order E2 (high) optical phonon mode reveal the spatial confinement of optical phonons.